Representations of the City. The Diffuse Museum The Esquilino Tales (diségno, 2021)
Various experiments in cultural heritage enhancement and education have been directed at defining new paradigms of experience, bringing actions and interactions of and between subjects back to the centre. This has led to renewed interest in experiences capable of integrating education and fun, because the emotional environment of playing and the method of “learn by doing” facilitates learning processes. In this context, we present The Esquilino Tales, conducted in the Master in Communication of Cultural Goods at the Sapienza University of Rome, which aims to enhance the varied, even identity-building complexity of the Esquilino area, the XV Rione of Rome. Since this is a place where both the whole and its individual parts are recognizable first as “figures”, the project began with the conviction that an effective proposal could only start with the specific signs of the places. The experimentation therefore investigated the practices of representation, innovating with them through the techniques of storytelling, gamification, and storydoing to develop a communication strategy using a wide range of graphical/visual languages. In this strategy, active means of exploration such as initial actions of enhancement and urban regeneration are proposed for activation between the visitors/citizens and Esquilino/city to begin to rescue our city.
Keywords: graphical languages; communication; enhancement; gamification; storytelling